". . . What Is Going On in the Lives of These People?": Encouraging Community Engagement in Development Economics Studies. (February 2019) - Claassen, Carike; Blaauw, Derick
To respond to the numerous socioeconomic challenges facing South Africa, universities must equip students to actively participate in economic development initiatives. Students from Economics and all disciplines in the Social Sciences have a pertinent role to play in this regard. This article presents an initiative to implement service learning as part of the curriculum for Development Economics students at undergraduate and postgraduate levels at a South African public university. Undergraduate and postgraduate students acted as fieldworkers who carried out survey research in the local informal economy in the university town of Potchefstroom in South Africa's North West Province. The experiences of students and lecturers in these two complimenting projects are compared and contrasted. The enthusiasm for the project was a clear theme emerging form the pilot projects. Future endeavors must employ even more resources to enable even more reflection in the learning experience. The possibility and benefits of converting the complete curriculum of Development Economics into a service learning approach also emerged from the research.